Análise das principais variáveis na flotação industrial do complexo de mineração de Tapira - MG - Silva, Fernando Brandão Rodrigues da (2016)
Faced with an agribusiness expansion scenario and the increase in fertilizer consumption due to the exponential growth of the population, it is necessary to make better use of existing reserves, by obtaining products of better quality and in adequate quantities to meet demand national. In Tapira Mining Complex, Vale Fertilizantes, the phosphate concentrate is produced with content of 35.0% P2O5 from ore with content of about 8.0% P2O5, which are intended to supply Complex Industrial Uberaba and Araxá Minero Chemical Complex for the production of fertilizers. The industrial flotation step responsible for the recovery of P2O5 and hence the viability of the business is divided into the crumbly, grainy and ultrathin circuits, and, friable and granular concentrate comprise the conventional concentrated. Today only 14.7% of the mass which feeds the mill product becomes, the remainder being considered losses in the process, and the larger mass losses are located in the waste of flotation, representing 42.3%. From 2012 to 2014, the daily global mass recovery processing plants varied from 12.4 to 15.9% while the daily metallurgical recovery of P2O5 from 48.7 to 82.4%. By the degree of variability, it appears that the plant operated under different conditions. Seen this, this study aimed to analyze the influence of operational and process variables in P2O5 mass and metallurgical recoveries of industrial flotation circuits of grainy, crumbly and ultrathin. And besides was made an analysis of the effect of ore variables, as degrees, hardnesse and the ore front 02 percentage, in global recoveries of processing plant and the effect of dosages of reagents in the recoveries obtained from the bench flotation using the experimental design methodology. All work was performed using the historical database of Vale Fertilizantes of Tapira-MG, where all independent variables were dimensionless as the experimental range used. To make the statistical analysis it used the response surface technique and the values of the independent variables that maximize recoveries were found by canonical analysis. In the study of industrial flotation circuit crispy were obtained from 41.3% mass recovery and 91.3% metallurgical recovery P2O5, good values for the circuit, and the highest recoveries occur for solids concentration of the new flotation power between 45 and 50%, which values are assigned to the residence time of the pulp in cells and industrial flotation columns. The greater the number of ore heaps resumed on the higher the mass recovery, but in this scenario flotation becomes unstable because there is enormous weight variation in the feed. Higher recoveries are obtained for mass depressant dosage exceeding 120 g / t for synthetic collector dosage of 11.6%. In the study of industrial flotation circuit of the granulate were obtained 28.3% to 79.4% mass recovery and metallurgical recovery of P2O5 being considered good values for the circuit. Higher recoveries are obtained when the front ore 02 percentage is above 90%, because the ore of this front have more clear apatite. Likewise recoveries increase when the level of pulp rougher step is highest due to the high mass of circulating step receives loads. In the analysis of industrial flotation circuit of the ultrafine were obtained 23.95% of mass recovery, and the same is maximized to depressant dosage and the top collector 420 and 300 g / t, respectively. The analysis of the influence of variables ore, it was observed that higher recoveries are obtained for ores with P2O5 content above 8.0%, Fe2O3 content in the order of 28% forward and 02 of ore percentage of 83%. Hard ore percentage has strong influence on recoveries due to mass division in the circuit that is linked to this variable. However, the hard ore percentage that maximizes recoveries was very close to the design capacity of the processing plant, which is 20%. Finally, the study of the bench flotation, has noted that in friable and granular circuits the highest recoveries are achieved for a collector dosage exceeding 250 g / t and the simultaneous increase of collector dosage and synthetic collector percentage contributes to the increase recovery in the flotation, but this scenario is suitable to produce a concentrate poorer in terms of P2O5 content, showing that higher recovery is not always the ideal scenario. Thus, the results show the values of variables that provide higher recoveries in the flotation and hence lower losses in the waste.